KETERAMPILAN DASAR MENGAJAR GURU PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DI SMPN 1 IV KOTO KABUPATEN AGAM - Tysa Sufia Rahmi (Journal of Civic Education, 2019)
This event will be based on research because there are still teachers who have yet to implement skills Pkn asked intact. ask skills is one of the basic skills that must be taught by each teacher dimiliPKn, because in every teaching and learning to ask students is the thing that can not be left by the teacher. with the ability to ask a teacher will be able to dig up the entire ability of students to think and could invite students to develop critical thinking and ability. Implementation of the teaching skills of teachers PKn SMP 1 IV Koto is still not fit properly, because not all of the indicators of basic skills teaching carried out by teachers as a whole on the implementation of the learning in the classroom. Factors that influence the teaching of basic skills teachers is the lack of awareness of teachers in improving teaching skills, lack of training obtained by teachers PKn SMP 1 IV Koto about teaching basic skills teacher.